Transmitting the Survivor's Voice: Redeveloping the Sydney Jewish Museum. Issue 3 (1st September 2016) - Alba, Avril
Abstract : As commemoration of the Holocaust passes from the generation of witness to succeeding generations, Holocaust museums have begun to embody a more self-conscious museology, accompanied by often-fierce internal, as well as public, debates. Increasingly influenced by both public and private intergenerational forces, these institutions must engage with the complex and often contested process of interpretation that defines a mediated, rather than immediate, relationship to the past. The following account of one such process, the redevelopment of the Sydney Jewish Museum's permanent Holocaust exhibition, clearly illustrates the contentious, yet productive nature of these endeavors, demonstrating that for a growing number of these institutions, the passing of the survivor generation marks not only a human and historical shift, but also a shift in the shape of memory itself.